Effect of Cry1F maize on the behavior of susceptible and resistant Spodoptera frugiperda and Ostrinia nubilalis. Issue 1 (26th February 2016) - Vélez, Ana María; Alves, Analiza P.; Blankenship, Erin E.; Siegfried, Blair D.
Abstract: Understanding the behavior of pests targeted with Bacillus thuringiensis Berliner (Bt) crops is important to define resistance management strategies. Particularly the study of larval movement between plants is important to determine the feasibility of refuge configurations. Exposure to Bt maize, Zea mays L. (Poaceae), has been suggested to increase larval movement in lepidopteran species but few studies have examined the potential for resistance to interact with behavioral responses to Bt toxins. Choice and no‐choice experiments were conducted with Spodoptera frugiperda (JE Smith) (Lepidoptera: Noctuidae) and Ostrinia nubilalis (Hübner) (Lepidoptera: Crambidae) to determine whether Cry1F resistance influences neonate movement. Leaf discs of Cry1F maize and the corresponding isoline were used to characterize behavioral responses. In both experiments, the location (on or off of plant tissues) and mortality of susceptible and Cry1F resistant neonates was recorded for 5 days, but the analysis of larvae location was performed until 7 h. Our results indicated no strong difference between resistant and susceptible phenotypes in S. frugiperda and O. nubilalis, although a small percentage of susceptible neonates in both species abandoned maize tissue expressing Cry1F. However, significant behavioral differences were observed between species. Ostrinia nubilalis exhibited increased movement between leaf discs, whereas S. frugiperda selected plant tissue within the first 30 min and remained on the chosen plant regardless of the presence of Cry1F. Spodoptera frugiperda reduced larval movement may have implications to refuge configuration. This study represents the first step toward understanding the effects of Cry1F resistance on Lepidoptera larval behavior. Information regarding behavioral differences between species could aid in developing better and more flexible resistance management strategies.